2019
DOI: 10.1038/s41598-018-37695-0
|View full text |Cite
|
Sign up to set email alerts
|

The differences of lipid profiles between only children and children with siblings: A national survey in China

Abstract: With the increasing number of the one-child family, it is important to investigate whether the only-child status is associated with dyslipidemia. Among a national sample of 65,347 Chinese children aged 6–17 years, 16,100 lipid profiles were available. Children’s height, weight, total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) were measured. In comparison to children with siblings, only children (OC) were more likely to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…The associations between the single children and an increased risk of elevated blood pressure (35), dyslipidemia (10), hypertension (13), abdominal obesity (11,35), overweight and obesity (36, 37) were confirmed in China and European countries. However, one study found the opposite results that children with siblings were associated with a higher risk of hypertension (12), which the authors believed was likely attributed to adjustments for BMI or obesity status.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The associations between the single children and an increased risk of elevated blood pressure (35), dyslipidemia (10), hypertension (13), abdominal obesity (11,35), overweight and obesity (36, 37) were confirmed in China and European countries. However, one study found the opposite results that children with siblings were associated with a higher risk of hypertension (12), which the authors believed was likely attributed to adjustments for BMI or obesity status.…”
Section: Discussionmentioning
confidence: 90%
“…Based on this, many studies have noted the impact of different family structures on CMRFs, as well as sex differences. Recent studies provided evidence for the association of single children with components of CMRFs such as dyslipidemia ( 10 ), abdominal obesity ( 11 ), and hypertension ( 12 ) in children and adolescents, however, the findings were inconsistent in the direction of the association and sex differences. In addition, only one Iranian study explored the association between single children and all components of CMRFs, and this positive association was mainly manifested in abdominal obesity ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Few prior studies have investigated the associations between sibship characteristics and lipid profile and reported mixed results [17][18][19][20]. Two studies have shown that lipid profile was not significantly different when comparing firstborns to laterborns [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the sibling effect on lipid profile using dichotomous approaches (e.g., firstborns versus laterborns or only-children versus children with siblings) [17][18][19][20], which did not allow to investigate a doseresponse relationship between lipid profile and sibship size or position of the child in the sibship. Such an approach will help to better uncover the true relationship between sibling effect and lipid profile and to understand the potential mode of action of siblings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation